2020
DOI: 10.5539/jas.v13n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar on Properties of Tropical Sandy Soils Under Organic Agriculture

Abstract: This study evaluated the influences of biochar made from local agricultural wastes on sandy soils in farmer fields where biochar has been used as a soil amendment for more than three years. The major objective of this study was to gain insight into the effects of long-term biochar application on properties of sandy soil. Unamended soil properties were compared to biochar-amended soils properties using the paired samples t-test (p < 0.05). The statistical results of the study indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…However, no Cd and Pb were detected by XRF for all samples. Experimental data of Prakongkep et al (2020) support the results of the present research that some biochar had higher Ca and lower K and vice versa . The DOC released from AC and biochars was in the range of 0.6–1.6 mg/L (see Table ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, no Cd and Pb were detected by XRF for all samples. Experimental data of Prakongkep et al (2020) support the results of the present research that some biochar had higher Ca and lower K and vice versa . The DOC released from AC and biochars was in the range of 0.6–1.6 mg/L (see Table ).…”
Section: Resultssupporting
confidence: 87%
“…of the present research that some biochar had higher Ca and lower K and vice versa. 43 The DOC released from AC and biochars was in the range of 0.6−1.6 mg/L (see Table 2). The surface area (SA) of BB was 191.95 m 2 /g, which was higher than those of MB (11.74 m 2 /g) and PSB (2.46 m 2 /g) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Organic soil supplements can help provide plants with an extra boost of nutrients by increasing the soil’s capacity to hold water and nutrients. Several studies have been conducted to improve soil–water relations using various applications, including biochar [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These improvements can affect nutrient cycles and soil structure, resulting in differences in plant growth and productivity. Prakongkep et al [ 5 ] found that biochar soil supplementation enhanced soil fertility and quality by enhancing water holding capacity, increasing cation exchange capacity, and retaining soil nutrients. Due to the high surface area and porous structure of biochar, its sustainable supplementation can positively influence the soil’s properties and water relations [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of biochar and its effect on the soil properties both in Slovakia and globally is not fully understood and requires further research. Published literature presents several examples [17,18] that biochar improves soil fertility, including nutrient regime and soil pH in coarse and acidic soils rather than in fine soils and soils rich in nutrients with alkaline pH. However, with farmer intervention, even coarse-textured soils can have higher pH and a good supply of nutrients.…”
Section: Introductionmentioning
confidence: 99%